Functional relationships between leaf hydraulics and leaf economics in response to nutrient addition in subtropical tree species - Villagra, Mariana (2013)
Leaves can be both a hydraulic bottleneck and a safety valve against hydraulic catastrophic dysfunctions, and thus changes in traits related to water movement in leaves and associated costs may be critical for the success of plant growth. A 4-year fertilization experiment with nitrogen (N) and phosphorus (P) addition was done in a semideciduous Atlantic forest in northeastern Argentina. Saplings of five dominant canopy species were grown in similar gaps inside the forests (five control and five N + P addition plots). Leaf lifespan (LL), leaf mass per unit area (LMA), leaf and stem vulnerability to cavitation, leaf hydraulic conductance (K(leaf_area) and K(leaf_mass)) and leaf turgor loss point (TLP) were measured in the five species and in both treatments. Leaf lifespan tended to decrease with the addition of fertilizers, and LMA was significantly higher in plants with nutrient addition compared with individuals in control plots. The vulnerability to cavitation of leaves (P50(leaf)) either increased or decreased with the nutrient treatment depending on the species, but the average P50(leaf) did not change with nutrient addition. The P50(leaf) decreased linearly with increasing LMA and LL across species and treatments. These trade-offs have an important functional significance because more expensive (higher LMA) and less vulnerable leaves (lower P50(leaf)) are retained for a longer period of time. Osmotic potentials at TLP and at full turgor became more negative with decreasing P50(leaf) regardless of nutrient treatment. The K(leaf) on a mass basis was negatively correlated with LMA and LL, indicating that there is a carbon cost associated with increased water transport that is compensated by a longer LL. The vulnerability to cavitation of stems and leaves were similar, particularly in fertilized plants. Leaves in the species studied may not function as safety valves at low water potentials to protect the hydraulic pathway from water stress-induced cavitation. The lack of rainfall seasonality in the subtropical forest studied probably does not act as a selective pressure to enhance hydraulic segmentation between leaves and stems.